Peningkatan Pengetahuan Perawatan Pasca Melahirkan melalui Pemberdayaan Kelas Ibu Hamil di Wilayah Kerja Puskesmas Bambanglipuro: Improving Postpartum Care Knowledge through Empowerment of Pregnant Women's Classes in the Bambanglipuro Community Health Center Work Area - Shalihah, Nusaibah Mar'atush; Wardayanti, Bernadetta Atik; Rhamadianto, Muhamad Iqbal; Hapsari, Hererapratita Aysha; Pratama, Rafika Surya Putra; Nurrohman, Muhib Zanuar; Shabirah, Hasna ‘Afifatun (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2025)
Pregnancy is a vital physiological process in a woman's life, during which a fetus develops in the uterus until delivery. However, high maternal mortality rate (MMR) and infant mortality rate (IMR) remain serious challenges, including in Bantul Regency, which has recorded relatively high MMR and IMR figures. One strategic effort to reduce these rates is through education in the form of Antenatal Care Classes (Kelas Ibu Hamil). This activity aims to increase pregnant women's knowledge of postpartum care, enabling them to navigate the postpartum period safely and independently. Evaluation was conducted using pre-test and post-test methods to measure the effectiveness of the education provided. The results showed a 10% increase in knowledge, indicating that participants were able to understand and implement the material delivered. Therefore, Antenatal Care Classes can serve as an effective educational medium to support the reduction of MMR and IMR at the community level.